Analysis of the Benefits of Palm Oil Waste for Improving Economic Welfare of Communities in Kualuh Hulu District - Kurniawan, Ervandy; Qarni, Waizul; Dharma, Budi (ITB AAS INDONESIA Surakarta, 2024)
Lidi, as a byproduct of palm oil, can be crafted into unique and appealing handicrafts that are in demand both domestically and internationally. With support from the government and local funders, these local products can achieve high market value. This study aims to understand the benefits of palm oil waste in improving the financial well-being of residents in Kualuh Hulu District. This research employs a descriptive qualitative method by conducting interviews with 15 experts, including lidi craftsmen, small collectors, and large collectors in Kualuh Hulu District. The results show that palm oil lidi is abundant in Kualuh Hulu, with an average monthly production of 24 tons and an annual production of up to 293 tons. Economic growth in Labuhanbatu Utara Regency also increased by 3.83% in 2022, driven by the agriculture, plantation, forestry, and fisheries sectors, which achieved the highest growth at 5.44%. The information and communication sector grew by 5.05%, and the financial services and insurance sector by 4.62%.